Pengaruh Likuiditas, Solvabilitas Dan Aktivitas Terhadap Profitabilitas Dengan Firm Size Sebagai Variabel Moderasi Pada Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di Bei 2017-2020 - Amartiya Dinda Wahyu Kirana; N. Rachma (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study was conducted to test whether the variables of Liquidity, Solvency, Activity on Profitability with Firm Size as Moderating Variables in Food and Beverage Subsector Companies Listed on the IDX for the 2017-2020 period. The population in this study amounted to 32 food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling technique used is purposive sampling and obtained as many as 12 companies as research samples. The research method used in this study is the normality test and the MRA test. The results showed that liquidity had a significant effect on profitability and solvency and activity had no significant effect on profitability. Firm size is not able to moderate the effect of Liquidity and Activity and is able to moderate the effect of Solvency. Keywords: Liquidity, Solvability, Activity, Profitability, Firm Size